2018
DOI: 10.1063/1.5027257
|View full text |Cite
|
Sign up to set email alerts
|

Annealing behavior of open spaces in AlON films studied by monoenergetic positron beams

Abstract: The impact of nitridation on open spaces in thin AlON x films deposited by a reactive sputtering technique was studied by using monoenergetic positron beams. For AlON x films with x ¼ 0%-15%, positrons were found to annihilate from trapped states in open spaces, which coexist intrinsically in an amorphous structure with three different sizes. Nitrogen incorporation into the Al 2 O 3 film increased the size of the open spaces, and their density increased as the post-deposition annealing temperature increased. T… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
7
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 18 publications
0
7
0
Order By: Relevance
“…34,35) Note that the recess-etched GaN (AlGaN) surfaces were exposed to nitrogen-based plasma at the initial stage of AlON deposition. Incorporating nitrogen into the Al-based oxide can stabilize its amorphous structure while preventing crystallization, 34,39) so relatively high post-deposition annealing at 800 °C was conducted to give the gate stacks good insulating and interface properties. Then, TiN electrodes were deposited by reactive sputtering and were patterned using conventional photolithography and etching techniques.…”
Section: Experimental Methodsmentioning
confidence: 99%
“…34,35) Note that the recess-etched GaN (AlGaN) surfaces were exposed to nitrogen-based plasma at the initial stage of AlON deposition. Incorporating nitrogen into the Al-based oxide can stabilize its amorphous structure while preventing crystallization, 34,39) so relatively high post-deposition annealing at 800 °C was conducted to give the gate stacks good insulating and interface properties. Then, TiN electrodes were deposited by reactive sputtering and were patterned using conventional photolithography and etching techniques.…”
Section: Experimental Methodsmentioning
confidence: 99%
“…Through this method, vacancy-type defects of various semiconductors (i.e., GaN, AlON x , CIGS) have been investigated. [22][23][24][25][26] Figure 1(a) shows the S parameters of BaSi 2 films grown at T S = 580 °C with various R Ba /R Si . We found that the optical properties changed markedly as R Ba /R Si values were varied, and the maximum photoresponsivity was achieved at R Ba /R Si = 2.2 for samples grown at T S = 580 °C, as shown in Fig.…”
mentioning
confidence: 99%
“…[1][2][3][4] Inserting a dielectric layer in such as MOS structures has been found to result in low leakage currents and high breakdown strengths. Numerous gate dielectrics, including SiN, 2,5) SiO 2 , 3,[6][7][8][9][10] Al 2 O 3 , 4,[11][12][13][14][15][16][17][18] AlON, 19) ZrO 2 , 20,21) HfO 2 , 20,22) Si x N x -SiO 2 , 1) SiO 2 -HfO 2 , 8) Al 2 O 3 -HfO 2 , 23) and Al 2 O 3 -TiO 2 bilayers, 24) (Al, Si)O, 25) and Al 2 O 3 /SiO 2 laminate 26) (forming AlSiO x ) have been studied for use in MOS units, and films of these materials are typically deposited via chemical vapor deposition or atomic layer deposition (ALD). ALD is the optimal approach to fabricating conformal films on three-dimensional structures, which is required when producing vertical GaN devices.…”
mentioning
confidence: 99%